ANALISIS KINERJA MODULASI RADIO MICROWAVE PADA AUTOMATIC MODULATION RADIO - Hasad, Andi; Bakri, Muhammad Amin; Hakim, Firman L (JREC (Journal of Electrical and Electronics), 2013)
The purpose of this research was to determine the performance characteristics throughmodulation 16QAM modulation and 32QAM based on the range and bandwidth capacity.This research provides benefits to users microwave radio systemsandwill discussaboutthemodulation16 QAMand 32QAMin automaticmodulation radioforreceivepower levels,transmit powerand large of bandwidth. Analysis oftheliteraturewill be donebydisplayingrelatedmaterialsthat have beendone by theprevious academic, as well asthetestingandfield observationstoobtainrealdatafrom the linkusing16QAMand32QAMmodulation.Keywords: microwaveradio, modulation,16QAM, 32QAM, bandwidth, receive power level,transmit power